340 and 250 GHz Schottky solid‐state heterodyne receiver arrays for passive imaging systems. Issue 6 (23rd March 2022) - He, Yue; Liu, Ge; Zhou, Jingshi; Huang, Kun; Jiang, Jun; Su, Wei
Abstract: Real‐time terahertz passive imaging systems are highly demanded in security checking application. In this paper, two four‐pixel receiver arrays for 340 and 250 GHz passive imaging systems are presented. As the core device of the front‐end of the receiving array, the low noise terahertz mixer is realized based on the enhanced Schottky diode model and low‐loss circuit structure. The minimum double side band (DSB) noise temperature of the separated 340 and 250 GHz mixers is 900 and 580 K, respectively, within the operational band‐width. Without considering fluctuation in the power gain, the calculated temperature sensitivity of 340 GHz receiver is 0.8 K with 40 GHz RF band. Finally, based on all‐solid‐state millimeter‐wave drive front end and reflector optics, a passive terahertz imaging system is completed. Less than 1 cm space resolution is achieved for 1–3 m object distances, and the distinct imaging to hidden threats is produced and made contrast among the two receiver arrays. The perfect imaging performances of the system verify the low noise characteristic of terahertz mixer. The Schottky solid‐state receiver array provides a cheap and feasible option for personal security screening.